Impact of enterprise digitalization on green innovation performance under the perspective of production and operation - Li, Hailin; Tang, Hongqin; Zhou, Wenhao; Wan, Xiaoji (Frontiers in Public Health, 2022)
How enterprises should practice digitalization transformation to effectively improve green innovation performance is related to the sustainable development of enterprises and the economy, which is an important issue that needs to be clarified. This research focuses on listed industrial enterprises, deconstructs enterprise digitalization into six digitalization features from the perspective of production operation, and uses multi-source heterogeneous data released from 2016 to 2020 to measure these features. A variety of machine learning algorithms are used to achieve the goals, including the cluster analysis to identify different digitalization transformation situation based on above features, and the decision tree algorithms to explore the complex relationship between groups of enterprise digitalization features and the green innovation performance. Through the above process, we draw some interesting conclusions: (1) The more advanced digitalization transformation the enterprises have, the more possibly the high green innovation performance can be achieved. (2) Digitalization innovation is the digitalization element with the strongest influence ability on green innovation performance. (3) As the advancement of digitalization transformation, enterprises should also focus on digitalization innovation input and digitalization operation output, otherwise they should pay attention to digitalization management and digitalization operation output.